The Regional Exhibition of 1912 at the Santa Cruz college in Valladolid: Moisés de Huerta and Ramón Núñez (TRIM. Tordesillas, revista de investigación multidisciplinar, 2020)
After the National Exhibitions of Spain, at the beginning of the 20th century some exhibitions of smaller scope, regional and local, were developed. The regionalist movement promoted exhibitions of that character, such as the famous one of Santiago in 1909, Jacobean holy year. Somehow, the Regional Exhibition held in Valladolid in 1912 seems to be a replica of the Santiago one. It was hosted at the hostel of the College of Santa Cruz, home of the School of Arts and Crafts. This paper specifies the process of its organization with attention to the two sculptors out of competition, Moisés de Huerta and Ramón Núñez.
Keywords: Regional Exhibition; Valladolid; 1912; Ramón Núñez; Moisés de Huerta